Nucleation behaviour of racemic and enantiopure histidine. Issue 47 (11th November 2021) - Harfouche, Lina C.; Clevers, Simon; Coquerel, Gérard; Rietveld, Ivo B.
Abstract : Small non-centrosymmetric domains are observed in the racemic crystal, due to the low nucleation activation energy of the conglomerate. Abstract : Nucleation of dl - and l -histidine is examined using induction time measurements and their nucleation rates have been deduced. Results indicate a much slower nucleation for the racemic form compared to the pure enantiomer form. The effect of temperature and supersaturation on the nucleation rate is also described. Classical nucleation theory (CNT) is used to determine the interfacial energy, the nucleation energy barrier, and the nucleus size for both compounds. The large difference between the nucleation rates for the pure enantiomer and the racemic compound have so far not led to satisfactory preferential crystallization; however second harmonic generation analysis demonstrates the presence of non-centrosymmetric domains embedded within the racemic crystals implying that improving control over the nucleation conditions may lead to more efficient preferential crystallisation and symmetry breaking.